Pengaruh Kinerja Keuangan dan Kepemilikan Institusional Terhadap Penghindaran Pajak - Saga, Baharuddin; Dalimunthe, Ibram Pinondang (Universitas Pamulang, 2024)
This paper aims to determine the effect of financial performance and institutional ownership on tax avoidance. The financial performance is proxied into two, which are debt to assets ratio and return on assets. The population in this study are consumer non-cyclicals companies listed on the Indonesia Stock Exchange for the period 2017-2021, as many as 98 companies. The research sample selection technique used purposive sampling method so that 21 companies were selected, with an observation year of 5 years, there were 105 observations in this study. The research method used is an associative method with a quantitative approach. The data analysis technique uses panel data regression analysis with Microsoft Excel and Eviews 12 tools. Data testing used is descriptive statistics, panel data regression model selection, classical assumption test, coefficient of determination, and hypothesis testing. Based on the results of the study, it is known that the debt to assets ratio, return on assets and institutional ownership jointly affect tax avoidance. Partially, debt to assets ratio has no effect on tax avoidance, return on assets affects tax avoidance and institutional ownership has no effect on tax avoidance.